Centro regional de atención y capacitación a víctimas del conflicto armado en la ciudad de Florencia Caquetá (2019)
The present written work consists, in the design of an equipment of regional scope, for the attention of the internal armed conflict victims, in condition of forced displacement, located in the city of Florencia Caquetá, that by means of the infrastructure, can solve the basic needs of the affected population group that are concentrated around: The psychosocial attention, health, education, feeding and shelter. For it, does an urban approach which structures complementary areas, for the development of activities focused on productive trainings like: Agricultural production, fish farming, fruit processing, vegetables and meat, in this way answering to the activities, with greater economic potential in the department.